Effect of the Fibre Orientation Angles on Stress Concentration Around Various Shapes of Hole in Laminated Composite Plate Subject to in - Plane Loading - Yasin Bilal; Qi’dan Dana; Al-Olimat Safa; Ayasrah Mo’men; Almasaeid Hatem (Civil and Environmental Engineering, 2023)
The current study employs the finite element method to compare stress concentration pertaining to a graphite / epoxy rectangular laminated composite plate that possess holes in different shapes. The hole enables redistributing in-plane stresses, impacts the stress concentration factor (SCF), and focuses maximum stress near the hole. The ANSYS program has been designed to be employed for parametric studies pertaining to plates that have a hole under uniaxial in-plane load. Analysis was done for angle-ply, four-layered symmetrically laminated rectangular plates that include different stacking sequences ± θ.